The recalibration of the European System of Financial Supervision in regard of the insurance sector: From dreary to dreamy or vice versa? - Jens Gal; Helmut Gründl (Goethe University Frankfurt, SAFE - Sustainable Architecture for Finance in Europe, 2017)
Coming (great) events cast their (long) shadow before. As the financial crisis gave birth to the creation of the European System of Financial Supervision (ESFS), the imminent Brexit now serves as an impulse to rather extensively reorganize it. Pursuant to the preferences of the Commission-as revealed in its draft for a regulation amending the regulations founding the European Supervisory Authorities (ESA)-the supervision (and regulation) of the financial sectors should be further centralized and integrated and additional powers should be given to the ESAs. To a large degree these alterations are intended to adjust the competences of the European Securities and Markets Authority (ESMA) to better meet its new objectives under the Capital Markets Union ('CMU'). In view that an equivalent to the CMU or the Banking Union-in the sense of a European Insurance Union-is not yet on the horizon for the insurance sector (or the occupational pensions sector), one could prima vista take the view that insurance supervision and regulation is once again taken captive by the necessity of regulatory reforms stemming from other financial sectors. However, even if that is partially the case, the outcome of the intended reforms might still be advantageous for the insurance sector and an important step in the right direction. Therefore, it needs to be intensively discussed. At this stage, some of the most prominent envisioned changes to the structure, tasks and powers of the European Insurance and Occupational Pensions Authority (EIOPA) and their necessity, usefulness or counter-productivity still have to be examined.
urn:nbn:de:hebis:30:3-451962
Keywords: 330; European Insurance Union; European Supervisory Authorities; EIOPA; European Insurance and Occupational Pensions Authority; Insurance Supervision